Debate: Making sense of the psychology of detention. A rejoinder to David Edwards - Solomons, Kevin (PINS-Psychology in Society, 2025)
Professor Edwards is hostile to psychoanalytic concepts and models, particularly as applied to the modern range of psychiatric disorders. On this basis he discounts the experience of those like myself for whom a psychoanalytic framework provides a measure of comprehension in the post traumatic stress disorder (PTSD). He seems to believe that his own preference for a cognitive-behavioural explanatory model automatically invalidates a psychoanalytic one, ironically and revealingly providing no evidence or arguments to support his personal preferences or to refute the model to which he is antagonistic.